Anaerobic power and cadence characteristics of elite cross-country and downhill mountain bikers - Hurst, H. T.; Swaren, M.; Hébert-Losier, K.; Ericsson, F.; Holmberg, H. C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Mountain biking (MTB) is composed of several sub-disciplines, with Olympic Cross-Country (XCO) and Downhill (DH) being the most popular. Much of the current research on MTB pertains to the aerobic demands of XCO racing, with comparisons often made to road cycling. No studies have compared elite level XCO and DH bikers. Therefore, the aim of this study was to investigate the anaerobic power and cadence characteristics of elite XCO to DH riders. Methods: Twelve male elite mountain bikers (n=6 XCO, n=6 DH; age 21.83 ± 3.71 yrs; stature 179.67 ± 4.40 cm; mass 72.50 ± 5.45 kg) took part in this study. An inertial load cycling test was performed as described in previous studies(3), on an SRM cycle ergometer instrumented with a scientific version SRM Powermeter. Inertial load was adjusted to ensure riders achieved 130-150 revs/min within 4-7 s. Peak power (Wpeak), cadence at Wpeak (CADopt) and power to weight ratio (W/kg) were calculated for each rider as the mean from 3 trials. Statistical differences between XCO and DH were determined using independent t-tests with significance set at p.0.05. Results: A significant difference between DH and XCO was found for CADopt (114.93 ± 5.41 and 107.96 ± 4.63 revs/min, p<0.05), respectively. No other differences were revealed between groups. The mean recorded values for DH and XCO were 1137.76 ± 135.84 and 1113.86 ± 75.22 W for Wpeak and 15.21 ± 2.05 and 15.95 ± 0.75 W/kg for power to weight ratio, respectively. Discussion: The findings of comparable Wpeak between groups may indicate that high anaerobic power is not a prerequisite for success in elite DH. However, significant differences were found in CADopt, where DH riders had a higher cadence when producing Wpeak compared to XCO riders. This may reflect training specificity and the greater emphasis on repeated accelerations in DH(2) and the lower cadences elicited by XCO riders(1). Further research is therefore warranted to compare laboratory and field-based performance in these two population groups.